Progression of Well-Differentiated Papillary Mesothelial Tumour to Mesothelioma in a Patient with Ehlers Danlos Syndrome - Sarita Prabhakaran; Matthew Hussey; Kenneth J. O'Byrne; Sonja Klebe (MDPI AG, 2021)
Well-differentiated papillary mesothelioma has been renamed well-differentiated papillary mesothelial tumour (WDPMT) in the current WHO classification because all mesotheliomas are now regarded as malignant. WDPMT is now defined as a non-invasive papillary mesothelial proliferation, with retained labelling for BAP1-desirable. The current WHO classification also includes mesothelioma in situ (MIS), which is defined as pre-invasive flat or papillary proliferation of mesothelial cells with a loss of BAP1 or MTAP. WDPMT has been variably defined in the past but was thought to occur more commonly in women and pursue a more indolent course than mesothelioma, but its progression to invasive disease has occasionally been reported. Here, we report a case of a 68-year-old woman with a history of asbestos exposure and an underlying diagnosis of Ehlers Danlos syndrome who was diagnosed with symptomatic WDPMT of the peritoneum that progressed to mesothelioma within two years. On retrospective analysis, the WDPMT showed a loss of BAP1. We suggest that a loss of BAP1 in WDPMT should be reported, since these lesions may show aggressive behaviour, and that they may best be regarded as similar to mesothelioma in situ.